2010
DOI: 10.1098/rstb.2010.0091
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of Lapita decoration do not support branching evolution or regional population structure during colonization of Remote Oceania

Abstract: Intricately decorated Lapita pottery (3100-2700 BP) was made and deposited by the prehistoric colonizers of Pacific islands, east of the main Solomon's chain. For decades, analyses of this pottery have focused on the ancestor-descendant relationships of populations and the relative degree of interaction across the region to explain similarities in Lapita decoration. Cladistic analyses, increasingly used to examine the evolutionary relationships of material culture assemblages, have not been conducted on Lapita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Intriguing patterns are emerging from the increasing numbers of studies using phylogenetic approaches to characterize cultural evolution [4,[9][10][11][12][13][14]. While many studies have identified cultural traits which are predominantly vertically or horizontally inherited, we develop a method able to elucidate the effects of the environment while acknowledging both of these evolutionary processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguing patterns are emerging from the increasing numbers of studies using phylogenetic approaches to characterize cultural evolution [4,[9][10][11][12][13][14]. While many studies have identified cultural traits which are predominantly vertically or horizontally inherited, we develop a method able to elucidate the effects of the environment while acknowledging both of these evolutionary processes.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic methods have shed light on the transmission of human culture, treating cultural traits as analogous to biological traits [6][7][8], and modes of inheritance of cultural traits are beginning to be ascertained for aspects of human culture. Those passed on vertically include some aspects of material culture [9,10] and family and kinship organization [4,11]; traits transmitted horizontally include cases of technical innovations [12], music [13] and other aspects of material culture [14].…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of contact among populations in Oceania has been validated and extended into the past by archaeologists. For example, Cochrane & Lipo [37] have shown that the Lapita people, who colonized most of Oceania, were in contact and engaged in sharing of material culture with one another for more than 200 years. By contrast, we suggest that neighbouring populations in continental settings should be expected to engage in less sharing.…”
Section: Discussionmentioning
confidence: 99%
“…In an analogous study not of linguistic vocabulary, but of stylistic variation in a particular material cultural tradition, Cochrane & Lipo (2010) explore the early population history of remote Oceania. They analyse design variation in the characteristic 'Lapita' pottery traditions of these initial colonists, highlighting some limitations of cladistic approaches if the history of such traditions was characterized by considerable inter-societal diffusion, and exploring network methodologies to identify such vectors of lateral transfer.…”
Section: Cultural Macroevolution As An Inverse Problemmentioning
confidence: 99%